Comparative study of evaluation techniques in physiology clinical practicals by objective structured practical examination verses traditional practical examination - Jiwane, Rekha; Jiwane, Sushil; Tiwari, Narendra; Gajbhiye, Vivekanand (International Journal of Research in Medical Sciences, 2023)
Background: Objective structural practical examination assesses students by evaluating their knowledge, attitude, communication skills, interpersonal skills, ethical issues and professional judgement. Objectives were to compare the traditional practical clinical examination with objective structured practical examination. To establish the relation between the TCE and OSPE. To take the feedback from students about the study. Methods: This interventional longitudinal study was conducted on 100 first-year medical students. They were divided into 4 practical batches each consisting of about 25 students. In TCE each student performed a clinical skill, followed by viva voce on the RS. Assessment of each student were done on the bases of overall performance. In OSPE, students were provided an OSPE map and a written instruction list before the start of the examinations, and they move from one station to another following the audible ring by the timekeeper. Three observation station, six unobserved stations with questions relates to the procedural stations arrange in physiology practical laboratory. An examiner was provided with prevalidated checklist to mark according to the observed procedure. Results: Marks obtained during OSPE mean was 11.07 was more effective than marks obtained during TCE mean was 8.34. Most of students strongly agreed that OSPE was well structured, performance based, more objective as compared to TCE. Conclusions: OSPE is a good tool for practical assessment as compared to TCE to improve students’ learning process.